Pathological fracture in fibrous dysplasia: a case report - Bambang Supriyadi (Universitas Gadjah Mada, 2022)
Fibrous dysplasia (FD) is described as a growth disorder characterized by the progressive replacement of normal bone elements by fibrous-osseus tissue. Bones affected by FD is presented with bone weakening and prone to pathological fracture. We reported a case of FD in an 8-years-old boy, who came to the hospital with pain in the upper right thigh after falling with bumps in his head and foot. An X-ray revealed a deformity as a diasteal scalloping with radiolucency lesions on one-third proximal of the right upper femur, greater trochanter, and lesser trochanter, with complete transverse discontinuity in the distal deformity. No similar lesion was found in the other bones. Bone structure and trabeculation in the deformity area has decreased and the cortex was thinning. On magnetic resonance imaging (MRI), bone size was enlarged, hypointense on T1WI and inhomogeneous hyperintense on T2WI. Fibrous dysplasia with a pathological fracture is a rare case. The appearance on the X-ray was diasteal scalloping with a ground-glass radiolucency represented with Shepherd's crook deformity. This lesion was accompanied by a pathological fracture (fragility fracture) on distal lesion. Fibrous dysplasia which characterized by bone developmental anomaly gave an inhomogeneous hypointense on T1W1 and hyperintense on T2WI.